Development of an IoT-Based Broiler Chicken Coop Air Quality Monitoring Prototype - Panangian Mahadi Sihombing; Maharani Putri; Tuti Adi Tama Nasution; Muhammad Fiza Lubis; Aulia Agung Dermawan; Muhammad Syahruddin (Journal of Applied Informatics and Computing, 2026)
Inadequate air quality in the cage causes broiler chickens to become stressed, resulting in suboptimal weight gain, even death, and crop failure. Adequate broiler chicken cage air quality parameters include: a temperature range of 22 °C to 32 °C (depending on the chicken's age), a humidity range of 45% to 65%, an O2 level of≥ 19.6%, an NH3 level of ≤ 10 ppm, a CO level of ≤ 10 ppm, and a CO2 level of ≤ 3,000 ppm. Therefore, a technology is needed to monitor the air quality of the chicken coop in near real time. Thus, farmers can provide appropriate and prompt handling to maintain good air quality in the chicken coop. The purpose of this research is to develop a prototype for monitoring the air quality of broiler chicken coops based on IoT. The method used is research and development (R&D) with a prototype manufacturing approach based on the Internet of Things (IoT). The prototype was developed using temperature and humidity sensors (DHT22), NH3, O2, CO, and CO2 sensors. Each sensor is connected to the ESP32, which processes the data and displays it on the liquid crystal display (LCD) and the Thingspeak dashboard. Prototype testing was conducted by comparing the measurement results with those from standard measuring instruments in a closed container. Based on the test results, the prototype measured air quality accurately. This is evidenced by the mean absolute error (MAE) values for each measurement result of the O2 sensor, CO sensor, CO2 sensor, DHT22 sensor, and A02YYUW sensor, which are 0.10 % Vol, 4.46 μmol/mol, 24.20 ppm, 0.71 °C, and 0.13 cm, respectively. Thus, this prototype offers an advantage in measuring air quality in near real time using IoT.